2008
DOI: 10.1038/onc.2008.60
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic expression of the forkhead box M1 transcription factor induces formation of lung tumors

Abstract: The forkhead box m1 (Foxm1 or Foxm1b) protein (previously called HFH-11B, Trident, Win or MPP2) is abundantly expressed in human non-small cell lung cancers where it transcriptionally induces expression of genes essential for proliferation of tumor cells. In this study, we used Rosa26-Foxm1 transgenic mice, in which the Rosa26 promoter drives ubiquitous expression of Foxm1 transgene, to identify new signaling pathways regulated by Foxm1. Lung tumors were induced in Rosa26-Foxm1 mice using the 3-methylcholanthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
82
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 47 publications
2
82
0
Order By: Relevance
“…Analogously, our results also show that the expression level of FOXM1 is increased both in CRC and CRA compared to NOR. The FOXM1 overexpression is essential for the development of various cancers (38,39) ranging from pancreatic (40), breast (41), non-small cell lung cancer (42) and basal cell carcinoma (43), to colorectal cancer (44). FOXM1 was found to be more intensively expressed in CRA than in CRC (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Analogously, our results also show that the expression level of FOXM1 is increased both in CRC and CRA compared to NOR. The FOXM1 overexpression is essential for the development of various cancers (38,39) ranging from pancreatic (40), breast (41), non-small cell lung cancer (42) and basal cell carcinoma (43), to colorectal cancer (44). FOXM1 was found to be more intensively expressed in CRA than in CRC (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…FOX protein function can either promote or inhibit tumorigenesis, and deregulation of FOX protein function in human tumorigenesis may occur by alteration in upstream regulators or genetic events such as mutations of the DBD, or translocations, which often disrupt the DBD (16). FOXM1 is overexpressed in human tumors (13,(17)(18)(19)(20)(21)(22) and promotes tumor growth (18,23,24). Inhibition of FOXM1 expression reduces growth of murine tumors in response to carcinogens, and diminishes DNA replication and mitosis of tumor cells (12,13,17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated that aberrant overexpression of Foxm1 in all cell types using ubiquitous Rosa26 promoter accelerated prostate carcinogenesis in TRAMP and LADY transgenic mice (31). Prostate cancer lesions contain a heterogeneous population of cells, which includes epithelial, inflammatory (macrophages, granulocytes), and stromal cells, all of each up-regulate Foxm1 expression during cancer formation (51).…”
Section: Discussionmentioning
confidence: 99%